2020
DOI: 10.1111/jfbc.13567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of walnut ( Juglans sigillata ) oil on intestinal antioxidant, anti‐inflammatory, immunity, and gut microbiota modulation in mice

Abstract: The study investigated the anti-oxidant, anti-inflammatory, immunity, and gut microbiota modulation in mice (n = 60; 15 mice/group) after intragastric administration of walnut oil (WO; three groups (low (LD), medium (MD), and high doses (HD): 2.5, 5, and 10 ml/kg, respectively) and normal control (NC, saline). WO significantly increased the median villous height/crypt depth (VH/CD) ratio, the activities of superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) in intestinal mucosa. WO exerted the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Previous studies indicated associations between the gut microflora composition and the antioxidative ability of the host. 13,50–52 A positive correlation of aortic NADPH oxidase activity and genus Turicibacter , which had been reported to increase in SHR, 20,47 was observed in our results. CCFM752 down-regulated this genus as well as the aortic NADPH oxidase activity in SHR, suggesting that the down-regulation of Turicibacter may contribute to the prevention of aortic oxidative stress and vascular dysfunction.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies indicated associations between the gut microflora composition and the antioxidative ability of the host. 13,50–52 A positive correlation of aortic NADPH oxidase activity and genus Turicibacter , which had been reported to increase in SHR, 20,47 was observed in our results. CCFM752 down-regulated this genus as well as the aortic NADPH oxidase activity in SHR, suggesting that the down-regulation of Turicibacter may contribute to the prevention of aortic oxidative stress and vascular dysfunction.…”
Section: Discussionsupporting
confidence: 84%
“…In recent years, the research on walnut oil has become popular because walnut oil is a kind of edible oil with high nutritional value. Walnut oil nutrition research mainly focuses on the role of walnut oil in intestinal diseases, which is widely used in traditional medicine around the world and is prescribed as beneficial food oil in agroindustry [ 5 ]. Walnut oil is a prominent functional food candidate for inflammatory bowel disease treatment [ 6 ] and ulcerative colitis treatment [ 7 ] because it has good antiaging activity in vivo [ 8 ] and can increase antioxidant capacity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results show that intestinal microorganisms can affect the antioxidant ability of the different organs. Miao et al (2021) found that it enhanced the GSH-Px activity in the small intestine of mice and increased the relative abundance of Lactobacillus after the 5 ml/kg walnut oil gavage test on mice ( Miao et al, 2021 ). In our experiment, we analyzed the correlation between intestinal oxidative stress and colonic microbial changes and found that there was a correlation between intestinal GSH-Px was positively correlated with Muribaculaceae , Peptostreptococcaceae , and Desulfovibrionaceae , suggesting that PMS may affect the activity of GSH-Px by increasing the abundance of Peptostreptococcaceae .…”
Section: Discussionmentioning
confidence: 99%